Integrating Coastal Lampung’s Bedana Dance into an Interactive Digital Module to Enhance Students’ Biological Literacy - Rita T. Marpaung , Rini; Agus Priadi , Median; Resti Amalia , Nafista; Yolida , Berti; Meriza, Nadya; Maulina , Dina; Estu Kinasih, Mufidah; Priyambodo, Panggih; Hasniza, Nor (Biosfer: Jurnal Tadris Biologi, 2025)
Coastal Lampung has a high level of cultural diversity, one example of which is the Bedana dance. This study aims to determine the feasibility and effectiveness of an interactive digital module integrating the local wisdom of the Coastal Lampung Bedana dance in improving students’ biological literacy. This research employed a Research and Development (R&D) method with Grade XI science students of a senior high school in Gedongtataan as the research subjects. The research data consisted of qualitative and quantitative data obtained through questionnaires, interviews, and tests. The validation results indicated that the interactive digital module was highly feasible for learning, with material feasibility of 93%, language 78%, media 93%, cultural aspects 89%, and practitioner assessment 100%. Limited trials obtained a positive response of 91%. The implementation test showed an N-Gain score of 0.72, categorized as high. The effectiveness test yielded a Sig. (2-tailed) value of 0.008, indicating a significant effect on students’ biological literacy. Modul Digital Interaktif Berbasis Kearifan Lokal Tari Bedana dalam Meningkatkan Literasi Biologi Peserta Didik ABSTRAK: Lampung Pesisir memiliki keanekaragaman budaya yang tinggi, salah satunya adalah tari Bedana. Penelitian ini bertujuan untuk mengetahui kelayakan dan efektifitas modul digital interaktif bermuatan kearifan lokal tari Bedana Lampung Pesisir terhadap literasi biologi peserta didik. Penelitian ini menggunakan metode penelitian dan pengembangan (Research and Development) dengan subjek siswa kelas XI IPA Sekolah Menengah Atas di Gedongtataan. Data penelitian berupa data kualitatif dan kuantitatif yang diperoleh melalui angket, wawancara, dan tes. Hasil validasi menunjukkan modul digital interaktif sangat layak digunakan dengan persentase kelayakan materi 93%, bahasa 78%, media 93%, budaya 89%, dan praktisi 100%. Uji coba terbatas memperoleh respons 91%. Hasil uji penggunaan menunjukkan nilai N-Gain literasi biologi sebesar 0,72 (kategori tinggi). Uji efektivitas memperoleh nilai Sig. (2-tailed) sebesar 0,008, yang menunjukkan pengaruh signifikan terhadap literasi biologi peserta didik.